Impact of Trade Liberalization on Economic Growth in Japan: Autoregressive Distributed Lag Model (ARDL) - Irene, Soh Chin Yee; Jerome, Kueh; Josephine, Yau Tan Hwang; Audrey, Liwan (Human Resource Management Academic Research Society, 2021)
The objective of this study is to identify the impact of trade liberalization on economic growth in Japan. Annual data are utilized from 1985 to 2016 via on Autoregressive Distributed Lag Model (ARDL) Cointegration test and Vector Error Correction Model (VECM) based Granger causality. The findings from unit root tests revealed that all the variables of mixed results whereby they are integrated at I(0) and I(1) and could proceed to the ARDL Cointegration test. Furthermore, all the variables have long-run relationships between trade openness, investment, education, inflation and economic growth in Japan. However, this study found a significant positive of trade openness and investment on economic growth in the long run. Lastly, VECM based Granger causality showed some of the causality relationships between variables in the short run for Japan.